Echoes of Despair: Translation Techniques in Dazai’s No Longer Human (International Journal of Education and Literature, 2025)
Osamu Dazai’s No Longer Human is one of the most devastating Japanese literature that portrays the inner turmoil of human beings in a very emotional way. The main character, Oba Yozo, is characterized by alienation, despair and identity crisis. This study is meant to identify the types of emotional expressions that appear in the original text and trace the translation techniques used in the two translated versions. The method used is descriptive qualitative with a comparative approach utilizing Molina & Albir’s translation technique theory and Nababan’s translation accuracy indicators. The analysis results show that Keene tends to use literal and amplification translation techniques to preserve the psychological depth of the characters, while Hanafi is more frequently employs modulation and reduction techniques with the aims of simplifying the language style. Some quotations also highlight differences in accuracy levels that impact the conveyance of emotions to readers. The conclusion of this study affirms that translation techniques not only influence sentence structure but also determine how readers interpret the internal conflicts of characters and the atmosphere of the story in the target text